Research on modal characteristics of shanghai metro vehicle car body - Tianjing Li (КНУБА, 2018)
This article takes the head vehicle body of Shanghai Metro Line 13 as the research goal, through the finite element analysis of the vehicle body, to view the structural characteristics of various parts of the car body. First of all, look at the relevant parameters of the car body, analyze its structure, save some parts that have little effect on the results, reasonably simplify the car body structure, and use UG to draw a simplified 3D head car model. The model was imported into the finite element analysis software Hyper Mesh, which was divided into grids, defined materials, defined units, and unit-giving materials. The analysis order and analysis mode were determined, and the modal analysis of the vehicle body structure was performed to see the results of the modal analysis. The body vibration pattern and natural frequency under different orders are obtained. Analysis and statistics can provide the theoretical basis for the optimization and design of the body structure.
Keywords: subway body; UG model; finite element model; modal analysis; 629.11:656.4(510)